2017
DOI: 10.1097/01.aoa.0000515758.57898.88
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Probability Scores of Placenta Accreta on Magnetic Resonance Imaging With Hemorrhagic Morbidity

Abstract: (J Clin Anesth. 2016;34:261–269) Owing to increases in both cesarean delivery rates and maternal age, the incidence of placenta accreta is rising. Placenta accreta is an abnormal form of placentation with increased depth of placental invasion that is associated with maternal hemorrhage and is an important cause of maternal death. The objective of this study was to assess whether routine stratification of antepartum magnetic resonance imaging (MRI) findings of abnormal placentation correlated with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…With a sensitivity of 96% for predicting hysterectomy, specific cutoff values have been proposed: 3.5 for the placenta accreta index derived from ultrasound, and 2.5 cm for the maximum dimension of invasion as determined by magnetic resonance imaging [27]. All our patients had an MRI because it allows us to better study the insertion of the placenta accreta [26].…”
Section: Resultsmentioning
confidence: 99%
“…With a sensitivity of 96% for predicting hysterectomy, specific cutoff values have been proposed: 3.5 for the placenta accreta index derived from ultrasound, and 2.5 cm for the maximum dimension of invasion as determined by magnetic resonance imaging [27]. All our patients had an MRI because it allows us to better study the insertion of the placenta accreta [26].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we also found an association of the previously reported MRI signs with severe blood loss and hysterectomy performance. However, in accordance with data from clinical studies, 24 we decided to use a higher cutoff value (>2000 ml) to define severe/massive hemorrhage. In addition to profound blood loss, we included other adverse clinical events that may occur during delivery and further compromise maternal peripartum outcome: bladder wall repair, prolonged operation time, and admission to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed MRI scores for the diagnosis of abnormal placentation, 34,35 but the association of these scores with poor pregnancy outcomes has not been tested. In a recent study, 24 the authors describe a method of assigning scores to MRI reports based on degrees of probability for the diagnosis of placental invasiveness; the produced MRI score failed to correlate with patients' hemorrhagic morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scoring system may be useful for predicting the risk of placenta accreta, but it does not reflect the risk of antenatal bleeding. Recently, many attempts have been made to detect the extent of placental invasion through uterine muscle layer through magnetic resonance image (MRI) [6,10,11]. However, the cost and inconvenience of MRI should be considered.…”
Section: Discussionmentioning
confidence: 99%